Involvement of S-type anion channels in disease resistance against an oomycete pathogen in Arabidopsis seedlings - Kurusu, Takamitsu (Commun Integr Biol, 2018)
Pharmacological indications suggest that anion channel-mediated plasma membrane (PM) anion efflux is crucial in early defense signaling to induce immune responses and programmed cell death in plants. Arabidopsis SLAC1, an S-type anion channel required for stomatal closure, is involved in cryptogein-induced PM Cl(−) efflux to positively modulate the activation of other ion fluxes, production of reactive oxygen species and a wide range of defense responses including hypersensitive cell death in tobacco BY-2 cells. We here analyzed disease resistance against several pathogens in multiple mutants of the SLAC/SLAH channels of Arabidopsis. Resistance against a biotrophic oomycete Hyaloperonospora arabidopsidis Noco2 was significantly enhanced in the SLAC1-overexpressing plants than in the wild-type, while that against a bacteria Pseudomonas syringae was not affected significantly. Possible regulatory roles of S-type anion channels in plant immunity and disease resistance against bacterial and oomycete pathogens is discussed.